2020
DOI: 10.1101/2020.03.30.016238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine Signaling in the Dorsomedial Striatum Promotes Compulsive Behavior

Abstract: Habits and compulsions are two aspects of behavior that often develop in parallel and together lead to inflexible responding. Both habits and compulsions are hypothesized to be involved in psychiatric disorders such as drug addiction and obsessive-compulsive disorder (OCD), but they are distinct behaviors that may rely on different brain circuitries. We developed an experimental paradigm to track the development of both habits and compulsions in individual animals while recording neural activity. We performed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 77 publications
3
15
0
Order By: Relevance
“…Van Slooten et al [ 45 ] suggested that higher sEBR, as a potential indicator of higher tonic dopamine levels, may reflect increased energetic demands for promotion of the exploratory behaviors towards novel options; lower sEBR, in turn, potentially reflecting lower tonic dopamine levels, may relate to energy conservation for a selection of options with known reward. In line with that, a recent study by Seiler et al [ 65 ] reported large individual differences in the compulsivity of mice associated with different strategies used by individual animals dealing with uncertainty on the experimental paradigm designed to track the development of habits and compulsions. Importantly, the authors showed that striatal dopamine signaling was a key part of the circuitry that drives compulsion [ 65 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Van Slooten et al [ 45 ] suggested that higher sEBR, as a potential indicator of higher tonic dopamine levels, may reflect increased energetic demands for promotion of the exploratory behaviors towards novel options; lower sEBR, in turn, potentially reflecting lower tonic dopamine levels, may relate to energy conservation for a selection of options with known reward. In line with that, a recent study by Seiler et al [ 65 ] reported large individual differences in the compulsivity of mice associated with different strategies used by individual animals dealing with uncertainty on the experimental paradigm designed to track the development of habits and compulsions. Importantly, the authors showed that striatal dopamine signaling was a key part of the circuitry that drives compulsion [ 65 ].…”
Section: Discussionsupporting
confidence: 54%
“…In line with that, a recent study by Seiler et al [ 65 ] reported large individual differences in the compulsivity of mice associated with different strategies used by individual animals dealing with uncertainty on the experimental paradigm designed to track the development of habits and compulsions. Importantly, the authors showed that striatal dopamine signaling was a key part of the circuitry that drives compulsion [ 65 ]. Taking the abovementioned into account, a negative association between sEBR and compulsive symptoms in the PIU group might reflect on the subtle dopamine functioning alterations.…”
Section: Discussionsupporting
confidence: 54%
“…Here, we tested naïve animals (as did Haber et al, 2000 in their original tracing study), but it is possible that different connectivity patterns in striato-nigro-striatal circuits would emerge after training. We and others (Hamid et al, 2021;Seiler et al, 2020;Willuhn et al, 2012) have observed that the in vivo patterns of DA axon activity and DA release in DMS and DLS change with training. The reason why DA signaling changes with training is not yet clear, but one exciting possibility is that plasticity in either direct or indirect striato-nigro-striatal circuits is responsible.…”
Section: Balancing Striatal Inhibition and Disinhibition Of Dopamine Neuronsmentioning
confidence: 69%
“…Although DA axonal fields in striatum are broad (Matsuda et al, 2009), there is topography within the nigro-striatal system that can allow for separate control of DA release in DMS and DLS (Farassat et al, 2019; Ikemoto, 2007; Joel and Weiner, 2000; Lerner et al, 2015). Indeed, DA neurons projecting to DMS and those projecting to DLS display distinct in vivo activity patterns (Brown et al, 2011; Hamid et al, 2021; Lerner et al, 2015; Seiler et al, 2020; Tsutsui-Kimura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, corticostriatal plasticity in the lateral striatum correlates with habitual responding (O’Hare et al, 2016), and human imaging studies have linked activity in lateral striatum (putamen) with habitual behaviors (Tricomi et al, 2009). However, this model could be somewhat oversimplified, as other studies suggest medial striatum could also contribute to inflexible behaviors (Malvaez et al, 2018; Seiler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%